Differentiated Caching for Improved QoS in Vehicular Content-centric Networks - Swaroopa, Korla; Rodda, Sireesha; Chilukuri, Shanti (International Journal of Computer Sciences and Engineering, 2025)
Vehicular networks facilitate safer and more comfortable travel, but pose several challenges due to high rates of mobility and poor link quality. Information Centric Networking (ICN) is a recently proposed network paradigm that improves performance of networks with content as the focus. In this paper, we propose a differentiated cache replacement scheme called D-cache for content centric vehicular networks. In D-cache, vehicular network traffic is divided into time-sensitive sensor data (S-data) and infotainment related data (I-data). Simulation results show that the proposed scheme improves both the cache hit ratio and the average content retrieval time even at high mobility rates for content centric vehicular networks